Research progress and future prospects of antimicrobial modified polyetheretherketone (PEEK) for the treatment of bone infections - Zhang, Ziyi; Shao, Junxing; Gao, Yu; Li, Yuhuan; Liu, Te; Yang, Modi (Frontiers in Bioengineering and Biotechnology, 2023)
Infection of the bone is a difficult problem in orthopedic diseases. The key and basis of the treatment of bone infection is the effective control of local infection, as well as the elimination of infection focus and dead cavities. The most commonly used approach utilized for the prevention and management of bone infection is the application of antibiotic bone cement. However, the incorporation of antibiotics into the cement matrix has been found to considerably compromise the mechanical characteristics of bone cement. Moreover, some investigations have indicated that the antibiotic release rate of antibiotic bone cement is relatively low. Polyetheretherketone (PEEK) and its composites have been considered to perfectly address the challenges above, according to its favorable biomechanical characteristics and diverse surface functionalizations. This article provides a comprehensive overview of the recent advancements in the antimicrobial modification of PEEK composites in the field of antibacterial therapy of bone infection. Furthermore, the potential application of PEEK-modified materials in clinical treatment was discussed and predicted.